Transient Decrease in Nursing Workload in a Cardiology Intensive Care Unit During the COVID-19 Pandemic: A Brazilian Ecological Study - Clesnan Mendes-Rodrigues; Jully Silva Dias Evaristo; Ana Laura Lima de Jesus; Galeno Vieira de Oliveira Junior; Iolanda Alves Braga; Maria Beatriz Guimarães Raponi; Fabiola Alves Gomes (COVID)
The COVID-19 pandemic has led to a general increase in the workload in Intensive Care Units (ICUs). The objective here was to analyze the nursing workload in a Cardiology ICU of a tertiary and teaching inner hospital in Brazil before and during the COVID-19 pandemic. A retrospective and ecological study was conducted. Nursing Activities Score mean by month (NAS-mm) data were collected from the unit’s opening in October 2014 until May 2023. The data were divided into pre-pandemic and pandemic periods, with the pandemic further divided into three phases/years. A workload decrease was observed during the pandemic and varied across different pandemic years. In the pre-pandemic period, the mean was 53.80 points (95%CI: 52.99; 54.60; n = 65), whereas during the pandemic, it was 52.02 points (95%CI: 50.88; 53.17; n = 39). The first year had the lowest mean workload at 50.94 points, followed by the second year with 48.37 points, while the third year had the highest with 55.82 points, exceeding the pre-pandemic period’s workload. Amid the COVID-19 pandemic scenario, a decrease in nursing workload was observed in the unit, only returning to reference values in the third pandemic year, possibly associated with patient and administrative profile changes.